Выражение 12х-(3х-5)+(9х-3) решить уравнение 4(х+0,2)=5х-3,8

gta1234657 gta1234657    3   28.02.2019 05:40    3

Ответы
romamarunp016li romamarunp016li  23.05.2020 16:37

12х-(3х-5)+(9х-3)=12х-3х+5+9х-3=2

 

4(х+0,2)=5х-3,8

4х+0,8=5х-3,8

4х-5х=-3,8-0,8

-х=-4,6

х=4,6

ПОКАЗАТЬ ОТВЕТЫ
uraalekseev1234 uraalekseev1234  23.05.2020 16:37

12х-(3х-5)+(9х-3)=12х-3х+5+9х-3=18х+2

 

4(х+0,2)=5х-3,8

4х+0,8=5х-3,8

-5х+4х=-3,8-0,8

-х=-4,6

х=4,6

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра

Популярные вопросы